2020
DOI: 10.1177/1074248420931624
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stent Restenosis and Thrombosis in Rabbits: The Effect of Antiplatelet Agents

Abstract: Background: The purpose of the study was the comparative assessment of ticagrelor and clopidogrel effects on carotid post-balloon injury (PBI) and on post carotid artery stenting (CAS) rate of in-stent restenosis (ISR) and in-stent thrombosis in atherosclerotic rabbits. Methods: Forty-eight New Zealand white rabbits on high-fat diet were randomized into 4 groups: A1: PBI and clopidogrel (30 mg/kg/d), A2: PBI and ticagrelor (21 mg/kg twice daily), B1: PBI, CAS, and clopidogrel (30 mg/kg/d), B2: PBI, CAS, and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, they discovered that ticagrelor was more effective on intra-stent thrombosis. 22 Another attempt proved no difference in ISR between the cilostazol group after the CAS procedure and the patients who underwent the standard procedure. 23 It was also stated that statins affected the regulation of carotid neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, they discovered that ticagrelor was more effective on intra-stent thrombosis. 22 Another attempt proved no difference in ISR between the cilostazol group after the CAS procedure and the patients who underwent the standard procedure. 23 It was also stated that statins affected the regulation of carotid neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 95%
“…However, no definitive results were reached. 22 Kadoglou et al 22 showed that the use of ticagrelor and clopidogrel had similar effects on ISR prevention. The effects of these agents on neointimal hyperplasia and ISR in rabbits undergoing CAS procedure could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54] An experimental study comparing the effects of clopidogrel vs. ticagrelor on post-balloon injury, in-stent restenosis and in-stent thrombosis in an atherosclerotic rabbit model undergoing carotid balloon injury ± CAS did not demonstrate any differences between the two antiplatelet agents. 55 Nevertheless, a drawback of ticagrelor as part of DAPT is its higher bleeding risk compared with clopidogrel. 53,54 Antiplatelet/antithrombotic treatment for patients with crescendo TIA/ stroke in evolution A crescendo TIA is defined as repetitive TIA episodes over hours or days followed by return to normal neurologic status.…”
Section: Antiplatelet/antithrombotic Treatment For Patients Undergoin...mentioning
confidence: 99%